A combined heat and green hydrogen (CHH) generator integrated with a heat network. (15th October 2021) - Burrin, Dominic; Roy, Sumit; Roskilly, Anthony Paul; Smallbone, Andrew
Graphical abstract: Highlights: Techno-economic analysis of the co-generation of green hydrogen and heat for district heating networks. Novel combined heat and hydrogen (CHH) generator concept which yields an overall system efficiency of 94.6%. Selling both hydrogen and heat resulted in a significant reduction in Levelized Cost of Hydrogen. Abstract: Combined heat and power (CHP) systems offer high energy efficiencies as they utilise both the electricity generated and any excess heat by co-suppling to local consumers. This work presents the potential of a combined heat and hydrogen (CHH) system, a solution where Proton exchange membrane (PEM) electrolysis systems producing hydrogen at 60–70% efficiency also co-supply the excess heat to local heat networks. This work investigates the method of capture and utilisation of the excess heat from electrolysis. The analysed system was able to capture 312 kW of thermal energy per MW of electricity and can deliver it as heated water at either 75 °C or 45 °C this appropriate for existing district heat networks and lower temperature heat networks respectively. This yields an overall CHH system efficiency of 94.6%. An economic analysis was conducted based on income generated through revenue sales of both hydrogen and heat, which resulted in a significant reduction in the Levelized Cost of Hydrogen.